(3OjhGf Ydj Hf haGs - (3GHf haG , Ydj Hf eMeO Hf eMeO GdbQTj GdCfUGQj GdTGPdj, CHh GdMSf,J (B807 (3g` s
(3ChdgG (B:s
(3MQa GdCda MbbJ YgOj, eMHJi hhdGFj HTghO JhMjOj hMce haGFj s
(3BNQgG (B:s
(3hddeUWai NeQ GdeMHg bO UaG TQHfG Hg CMdi ef Gdef hGdSdhi s
(3fSNI KGfjIs
(3hhQO CjVkG JMJ Qbe (B461s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B164 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B769s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI NOGHNT HJfg (B(1774) s
Keywords: (3GdCOHs